The appeal without grievance in constitutional proceedings - Polanco Gutiérrez, Carlos Enrique (2025)
The purpose of this research is to critically analyze the position adopted by the 2023 National Jurisdictional Plenary on Constitutional and Procedural Constitutional Law, which suggests that judges resolve appeals even when the procedural party has failed to present specific grievances. To this end, the dogmatic method will be used to analyze the concept of appeal, its purpose, its requirements, and the nature and significance of the grievance. Additionally, the exegetical method will be employed to engage with the various contradictory case laws regarding the requirement of the grievance. Finally, through the comparative method, the Colombian experience on the matter will be explored.